SIMcheck: a toolbox for successful super-resolution SIM imaging - Ball, G; Demmerle, J; Kaufmann, R; Davis, I; Dobbie, I; Schermelleh, L (Nature Publishing Group, 2015)
Three-dimensional structured illumination microscopy (3D-SIM) is a versatile and accessible method for super-resolution fluorescence imaging, but generating high-quality data is challenging, particularly for non-specialist users. We present SIMcheck, a suite of ImageJ plugins enabling users to identify and avoid common problems with 3D-SIM data and assess resolution and data quality through objective control parameters. Additionally, SIMcheck provides advanced calibration tools and utilities for common image processing tasks. This open-source software is applicable to all commercial and custom platforms and will promote routine application of super-resolution SIM imaging in cell biology.